Contributions of Nonhuman Primates to Research on Aging. (March 2016) - Didier, E. S.; MacLean, A. G.; Mohan, M.; Didier, P. J.; Lackner, A. A.; Kuroda, M. J.
Aging is the biological process of declining physiologic function associated with increasing mortality rate during advancing age. Humans and higher nonhuman primates exhibit unusually longer average life spans as compared with mammals of similar body mass. Furthermore, the population of humans worldwide is growing older as a result of improvements in public health, social services, and health care systems. Comparative studies among a wide range of organisms that include nonhuman primates contribute greatly to our understanding about the basic mechanisms of aging. Based on their genetic and physiologic relatedness to humans, nonhuman primates are especially important for better understanding processes of aging unique to primates, as well as for testing intervention strategies to improve healthy aging and to treat diseases and disabilities in older people. Rhesus and cynomolgus macaques are the predominant monkeys used in studies on aging, but research with lower nonhuman primate species is increasing. One of the priority topics of research about aging in nonhuman primates involves neurologic changes associated with cognitive decline and neurodegenerative diseases. Additional areas of research include osteoporosis, reproductive decline, caloric restriction, and their mimetics, as well as immune senescence and chronic inflammation that affect vaccine efficacy and resistance to infections and cancer. The purpose of this review is to highlight the findings from nonhuman primate research that contribute to our understanding about aging and health span in humans.